Inventarisasi Tumbuhan Paku (Pterydophyta) Di hutan Batu Tikar Kecamatan Luwuk Kabupaten Banggai - Karim, Wahyudin Abdul; Nurlia, Nurlia; Ndolan, Yospina; Samaduri, Alwia (Jurnal Biologi Babasal, 2022)
Ferns are one of the plants that compile vegetation. They are often found in temperate and humid climates such as forests. In Batu Tikar Forests, Luwuk District, Banggai Regency has many types of plants, both high and low level. Low-level plants found in Batu Tikar Forest, Luwuk District, Banggai Regency include ferns (Pteridophyta). This reserach is to find out the result of ferns (Pteridophyta) inventory in Batu Tikar Forest, Luwuk District of Banggai Regency. The research design was descriptive explorative whis was conducted on July up to August 2020 in Batu Tikar Forest, Luwuk District of Banggai Regency. The research population were all ferns (Pteridophyta) and sample of this research is ferns which are found around the river flow to the left and right along 10 meters with the entire length of the river was 478 meters. Data collection was carried out using the exploration or cruise method. The ferns data collected were analyzed descriptively qualitatively by describing the morphological characteristics of the ferns. The results of this research showed that ferns (Pteridophyta) were found 30 types there are Adiantum sp. 1, Adiantum sp. 2, Pteris sp., Asplenium sp. 1, Asplenium sp. 2, Asplenium sp. 3, Asplenium sp. 4, Asplenium sp. 5, Asplenium sp. 6, Selaginella willdenowii (Desv.) Bak., Cyclosorus sp. 1, Cyclosorus sp. 2, Cyclosorus sp. 3, Cyclosorus sp. 4, Thelypteris sp.1, Thelypteris sp.2, Thelypteris sp.3, Christella sp., Orthioptheris sp., Nephrolepissp. 1, Nephrolepis sp. 2, Microsorum sp., Lastreopsis sp., Diplazium sp., Dicranopteris sp., Dyplazium sp., Stenosomia sp. Heterogonium sp., Dryopteris sp., Davallia sp. Keywords: Inventory, Pteridophyta, Batu Tikar forest